Pengaruh Pemahaman Peraturan Pajak, Sosialisasi Pajak, dan Tingkat Kepercayaan Terhadap Kepatuhan Wajib Pajak UMKM: Survei Pada Pedagang Di Kota Medan - Verico Simbolon; Remista Simbolon (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
. The purpose of this research is to ascertain how taxpayer compliance in micro, small, and medium-sized businesses (MSMEs) is impacted by knowledge of tax laws, tax socialization, and trust levels. By distributing questionnaires to MSME owners in Medan City, data was gathered for this study using primary data. There were 76 taxpayers used as samples in this investigation. The author uses multiple linear regression analysis, classical assumption testing, hypothesis testing, coefficient of determination analysis, and descriptive statistical analysis to process the data. The findings indicated that while tax socialization and comprehension of rules had little bearing on MSME taxpayers' compliance levels, trust levels significantly impacted MSME taxpayers' compliance levels.